Successful Therapy in A 20 Years Old Male with Acute Pancreatitis - Asri Nugraheni; Supriono Supriono (The Indonesian Society for Digestive Endoscopy, 2017)
Acute pancreatitis is an inflammation at pancreas that can be caused by biliary tract disease, alcohol and metabolic disorder. We presented a 20 years old male with acute pancreatitis, he was obese and had history of alcohol abuse came with severe abdominal pain. There is increasing amylase and lipase level, and his abdominal CT scan showed infiltrate peripancreatic, mesenteric, and left anterior pararenal space, hepatomegaly and mild ascites. Patient was given supportive treatment such as parenteral nutrition, analgetic, PPI, and also octreotide. With proper diagnosis and optimal treatment, patient was successfully treated without any complication.